2013
DOI: 10.1186/1743-8977-10-27
|View full text |Cite
|
Sign up to set email alerts
|

Internalization and cytotoxicity of graphene oxide and carboxyl graphene nanoplatelets in the human hepatocellular carcinoma cell line Hep G2

Abstract: BackgroundGraphene and graphene derivative nanoplatelets represent a new generation of nanomaterials with unique physico-chemical properties and high potential for use in composite materials and biomedical devices. To date little is known about the impact graphene nanomaterials may have on human health in the case of accidental or intentional exposure. The objective of this study was to assess the cytotoxic potential of graphene nanoplatelets with different surface chemistry towards a human hepatoma cell line,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
274
3
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 350 publications
(300 citation statements)
references
References 67 publications
19
274
3
4
Order By: Relevance
“…Advanced REACH Tool (ART) (Fransman et al, 2009) Occupational exposure assessment (Gorman et al, 2012) Occupational/consumer exposure assessment (Gottschalk et al, 2010a, 2010b, Sun et al, 2014, Gottschalk et al, 2009, Gottschalk et al, 2011 (Yokel et al, 2009, Yokel et al, 2012, Hardas et al, 2010, Dan et al, 2011 In vivoIkinetic tools for human exposure and hazard assessment (Lammel et al, 2013, Lammel andNavas, 2014) In vitro and in vivo tools for human hazard assessment…”
Section: Control Banding and Risk Screening Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Advanced REACH Tool (ART) (Fransman et al, 2009) Occupational exposure assessment (Gorman et al, 2012) Occupational/consumer exposure assessment (Gottschalk et al, 2010a, 2010b, Sun et al, 2014, Gottschalk et al, 2009, Gottschalk et al, 2011 (Yokel et al, 2009, Yokel et al, 2012, Hardas et al, 2010, Dan et al, 2011 In vivoIkinetic tools for human exposure and hazard assessment (Lammel et al, 2013, Lammel andNavas, 2014) In vitro and in vivo tools for human hazard assessment…”
Section: Control Banding and Risk Screening Toolsmentioning
confidence: 99%
“…cell membranes, metabolism and clearance mechanisms (Lammel et al, 2013). These tools aim to prioritize MNs for further testing and to determine realistic exposure concentrations to be applied in in vivo testing.…”
Section: Hazard Assessment Toolsmentioning
confidence: 99%
“…65,77 For instance, mitochondrial depolarization is associated with mitochondrial dysfunction and the overproduction of ROS. 68,78 Recently, Mari et al 30 reported that GO nanoribbons induced toxicity in human neuroblastoma cancer cell lines such as SK-N-BE(2) and SH-SY5Y. Altogether, the combination of GO and AgNPs in a single platform such as GO-AgNPs could modulate the regulation of mitochondria and increase the generation of ROS.…”
Section: Go-agnps Enhance the Generation Of Ros In Sh-sy5y Cellsmentioning
confidence: 99%
“…67 Other studies showed that exposing cells to GO results in the perturbation of the mitochondrial structure and function, as characterized by a decrease in the MMP and the dysregulation of mitochondrial Ca 2+ homeostasis. 68,69 Similarly, nano-sized GO, pristine graphene, and graphene quantum dots caused time-and concentration-dependent decreases in the MMP. 70,71 Altogether, the data from our findings clearly indicate that GO-AgNPs could cause mitochondrial dysfunction through loss of MMP.…”
Section: Effect Of Go-agnps On Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Ultrathin sections of cells were analyzed by TEM to reveal the intracellular accumulation/distribution of NPs and possible ultrastructural modifications. The method used has been described in Lammel et al (2013), which is briefly shown in the Supplementary Materials. A JEOL 1010 JEM (JEOL) microscope operating at an acceleration voltage of 100 kV with integrated energy dispersive X-ray (EDX) spectroscopy (Oxford INCA) was used.…”
Section: Microscopy Analysesmentioning
confidence: 99%